2011
DOI: 10.1016/j.ijgo.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of follicle loss after laparoscopic excision of endometrioma compared with benign nonendometriotic ovarian cysts

Abstract: In up to 92% of the cystectomy samples, normal ovarian tissue was found adjacent to the benign cyst; however, functional follicle loss was slightly, but significantly, higher in the endometriomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…In the present study, a total of 22 patients underwent surgery by laparoscopic ovarian cystectomy. Benign ovarian cysts such as ovarian endometrioma are common in young women, so the technique used for surgery is crucial for sparing ovarian tissue and residual ovarian function after operation is important [17]. The present study was attempted to investigate the influence of ovarian cystectomy on the ovarian reserve by assessing the levels of serum FSH, E2 and AMH, AFC and ovarian volumes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, a total of 22 patients underwent surgery by laparoscopic ovarian cystectomy. Benign ovarian cysts such as ovarian endometrioma are common in young women, so the technique used for surgery is crucial for sparing ovarian tissue and residual ovarian function after operation is important [17]. The present study was attempted to investigate the influence of ovarian cystectomy on the ovarian reserve by assessing the levels of serum FSH, E2 and AMH, AFC and ovarian volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a considerable amount of ovarian tissue containing follicles is unintentionally removed during cystectomy, which leads to the decrease in ovarian reserve [23,25]. The removal of any benign cyst inadvertently leads to the removal of ovarian tissue, but the effect is more significant in endometriomas [17]. Muzii et al [25] proposed that this difference was due to the presence of a pseudocapsule in an endometrioma versus a real capsule in a non-endometriotic cyst, which had a separate tissue plane making the dissection from tissue easy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective analysis we recently demonstrated that the stripping technique removes normal ovarian tissue in up to 90% of the cases both in endometriotic and nonendometriotic ovarian cysts. However, tissue loss was more in endometriotic cysts (14). Similarly, Roman et al (15) performed a retrospective study in 35 patients with endometriomas and concluded that there was normal ovarian tissue found in 97% the specimens.…”
Section: Serum Amh Level (Ng/ml)mentioning
confidence: 95%
“…More recent studies have demonstrated, by serial section, the presence of adjacent ovarian tissue in more than 90% of excised endometrioma wall specimens-and the larger the cyst diameter, the more tissue is removed (21,22).…”
Section: Arguments Against Surgerymentioning
confidence: 99%